2021
DOI: 10.1556/2006.2020.00100
|View full text |Cite
|
Sign up to set email alerts
|

Impaired disengagement of attention from computer-related stimuli in Internet Gaming Disorder: Behavioral and electrophysiological evidence

Abstract: Background and aims: Attentional biases contribute to the maintenance of addictive behaviors. For the problematic use of online gaming – recognized as Internet Gaming Disorder (IGD) – first evidence points to a bias towards in-game stimuli. This study aimed to provide behavioral and electrophysiological evidence for a generalized bias towards computer-related stimuli, and to identify the specific attentional processes contributing to this bias: facilitated attention deployment, impaired disengagement or failed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…Distraction frequency has been associated with attention impulsiveness, which is triggered by anxiety and takes the form of attentional bias (23), as has been supported in the smartphone and social media use literature (101,249,251). Attention impulsiveness has also been associated with habitual checking (121), chronic media multitasking and attention decrements (12) as well as with impaired disengagement in Internet Gaming Disorder (IGD) (252). In conditions where learning is of low interest, attentional impulsivity is associated with increased interruptions, reduced lecture comprehension, low motivation, and fluid intelligence (35,36), to the detriment of academic performance and tasks requiring sustained attention (37).…”
Section: Discussionmentioning
confidence: 89%
“…Distraction frequency has been associated with attention impulsiveness, which is triggered by anxiety and takes the form of attentional bias (23), as has been supported in the smartphone and social media use literature (101,249,251). Attention impulsiveness has also been associated with habitual checking (121), chronic media multitasking and attention decrements (12) as well as with impaired disengagement in Internet Gaming Disorder (IGD) (252). In conditions where learning is of low interest, attentional impulsivity is associated with increased interruptions, reduced lecture comprehension, low motivation, and fluid intelligence (35,36), to the detriment of academic performance and tasks requiring sustained attention (37).…”
Section: Discussionmentioning
confidence: 89%
“…As a unique behavioral addiction, IAD shares neural vulnerabilities with drug addiction and gambling addiction. Zhou and his colleagues tested whether individuals with IAD presented similar characteristics of working memory, executive function, and impulsivity to those presented by pathological gambling (PG) patients [ 18 ]. The results suggested that individuals with IAD and PG patients present deficiencies in working memory, executive dysfunction, and impulsivity, and individuals with IAD are more impulsive than PG patients.…”
Section: Discussionmentioning
confidence: 99%
“…Converging evidence suggests that IAD is associated with various changes in cognitive functions, such as perception [ 15 , 16 ], attention [ 17 , 18 , 19 ], memory [ 20 ], and executive function [ 2 , 7 , 20 ]. Inhibitory control, one of the executive functions, emerged as an important aspect of IAD [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be because of the conceptual distinction between facilitated attentional engagement with gaming-related stimuli (reflecting a disproportionate tendency for attention to be captured by gaming-related stimuli), and impaired attentional disengagement from gaming-related stimuli (reflecting an excessive predilection for attention to be held by gaming-related stimuli). Specifically, Heuer et al (2021) found that IGD gamers demonstrated longer reaction times than casual gamers. Further, they demonstrated increased sustained posterior contralateral negativity (SPCN) amplitude to computer-related stimuli in a visual search task, indicating that the disengagement of attention from addiction-related stimuli was impaired in IGD individuals.…”
mentioning
confidence: 99%
“…Theories posit that a combination of external and internal factors contributes to game craving and addiction development ( Brand, Young, Laier, Wölfling, & Potenza, 2016 , 2019 ). Game craving has been conceptualized as an outcome of classical conditioning ( Heuer, Mennig, Schubö, & Barke, 2021 ). Specifically, when environmental cues (e.g., the sight of game advertisements and the sound of game characters) have been repeatedly associated with playing games, they become conditioned stimuli that elicit gaming urges.…”
mentioning
confidence: 99%